PERBEDAAN WAKTU PENGELUARAN ASI TERHADAP INISIASI MENYUSUI DINI PADA IBU POSTPARTUM DI 2 KLINIK BERSALIN MEDAN JOHOR TAHUN 2014 - Syahrul Khairati (Jurnal Maternitas Kebidanan, 2018)
In Indonesia only 4% of infants are breastfed within the first hour after birth, said 21,000 new infant deaths under 28 days in Indonesia can be prevented through breastfeeding in the first hour after birth. early initiation in the first hour of post-birth down 22% risk of dying 0-28 days. When starting after (after the first day), it can increase the risk of death 2-4 times. The type of research used is an analytic study with cross sectional study design. This design aims to determine the difference in breastfeeding time to initiate early breastfeeding in postpartum mothers in Maternity Clinic Medan Johor. Sampling method of this research is by total sampling that is as much as 54 respondents with data analysis done using univariate and bivariate analysis with chi square test. The results showed that there was a significant relationship between breastfeeding expenditure and initiation of early breastfeeding in Postpartum Mother in 2 Maternity Clinic of Medan Johor. It is recommended that the Maternity Clinic to involve various parties such as health workers in this case midwives as a provider of breast care in the preparation of breastfeeding and the importance of initiation of early breastfeeding as a first step to the smooth expenditure of breastfeeding.